Independence Curriculum Implementation Challenges: A Case Study in Secondary School of Bengkulu Tengah - Puspitasari; Ira Maisarah (Journal of English for Specific Purposes in Indonesia, 2025)
The main goal of this study is to determine the difficulties that SMPN 18 Bengkulu Tengah, SMPN 14 Bengkulu Tengah, and SMPN 29 Bengkulu Tengah face in implementing the Merdeka Curriculum. This study employed a case study methodology and a qualitative research strategy. Six English teachers, the principal, and members of the school curriculum staff participated in this study. The results indicate that the teacher encountered challenges in implementing independent curriculum, including the provision of learning materials, the adjustment of students' learning styles, the creation of assessments, and the lack of adequate ICT resources. These findings highlight the need for improved resource allocation and support to ensure successful curriculum implementation.